Diverse Immunoregulatory Roles of Oxysterols - The Oxidized Cholesterol Metabolites - Finlay, David (My University, 2020)
Intermediates of both cholesterol synthesis and cholesterol metabolism can have diverse roles in the control of cellular processes that go beyond the control of cholesterol homeostasis. For example, oxidized forms of cholesterol, called oxysterols have functions ranging from the control of gene expression, signal transduction and cell migration. This is of particular interest in the context of immunology and immunometabolism where we now know that metabolic processes are key towards shaping the nature of immune responses. Equally, aberrant metabolic processes including altered cholesterol homeostasis contribute to immune dysregulation and dysfunction in pathological situations. This review article brings together our current understanding of how oxysterols affect the control of immune responses in diverse immunological settings.
PUBLISHED
Keywords: Oxysterols; Cholesterol; SREBP; LXR; GPR183; ROR; SERM; Ch25h; Cyp27a1; Inflammation; Cancer; Infection; Obesity; Autoimmunity; Endometriosis; Immunometabolism; Cancer; Immunology, Inflammation & Infection; Immune regulation; Immunometabolism; LXR; Oxysterols; Sterol regulatory element binding protein (Srebp)